Examining the trend of the research on Islamic financial literacy from 2016-2023: a bibliometric review - Kaweesa, Yusuf; Rosman, Romzie; Mohd Yusoff, Syarah Syahira (IIUM Press, 2024)
The purpose of this study is to identify the dynamics of research literature production in the field of Islamic financial literacy by conducting a bibliometric review. Indeed, this would aid in providing directions for future theoretical and empirical research and identifying the most influential work and authors in the field. A systematic literature search using the Scopus database was carried out and gathered a total of 35 publications from 2016-2023, published in 33 peer-reviewed journals, 1 book series, and 1 conference proceeding on which the researchers carried out descriptive statistics and content analysis. There were 32 articles, 2 conference papers, and 1 review. A comma-separated value (CSV) file containing 35 references was used for analysis on Vos Viewer from 2016 to 2023 to reveal thematic clusters. The literature search was done using seven keywords namely, “Islamic Financial Literacy”, “Shariah financial literacy”, “Sharia financial literacy”, “Shariah financial education”, “Sharia financial knowledge”, “Islamic financial knowledge”, “Islamic financial education”. This study revealed that there were four main aspects covered in the reviewed literature. These were basic concepts in measuring Islamic financial literacy, Islamic financial literacy as a determinant of adoption of Islamic banking, measuring the level of Islamic financial literacy, and determinants of Islamic financial literacy. Future research should be focused on analyzing the effect of Islamic financial literacy as a mediator or moderator of other factors of Islamic banking adoption. Indeed, this would help to fill the literature gap by fu